Diagnosis of meta-cognitive resources in athletes of bádminton(Original) (Revista científica Olimpia, 2017)
The meta-cognitive resources must emerge like mechanisms of error checking and revision of the strategy of sports learning accomplishing compensations that be shown at the analysis of the execution and the appraising control. One point of important departure constitutes it precisely establishing a diagnosis that the sports learning have like center meta-cognitive correlated resources. They utilized the following methods of the empiric level for the attainment of the proposed objective: The questionnaire No.1 to diagnose the meta-cognitive resources that express the conceptual aspect or meta-knowledge and the No 2 that you evaluate the functional aspects or her instrumentses same, the same way that you interview her. These instruments were applied to 6 athletes' sign of badminton of category 13-15 of the municipality Jiguaní, that way I eat two exercise machines of sports. The obtained results revealed a low level of development of the resources in almost the totality of the sign.
Keywords: Meta-cognition; meta-cognitive resources; sports learning; badminton.